Risk factors associated with cesarean section and adverse fetal outcomes in intrahepatic cholestasis of pregnancy - Kong, Chengcai; Zhu, Zonghao; Mei, Fenglin (Frontiers in Pediatrics, 2023)
Background: To determine the risk factors for cesarean section (CS) and adverse fetal outcomes (AFOs) in patients with intrahepatic cholestasis of pregnancy (ICP) based on the severity of maternal hypercholanemia. Methods: A hospital-based retrospective cohort study was performed between January 1, 2015, and December 31, 2019. A total of 227 nulliparous women with a singleton fetus complicated by ICP were included. The patients were divided into two groups according to the levels of total bile acids, that is, mild (10 μmol/L < total bile acids < 40 μmol/L) and severe (≥40 μmol/L). The patients’ clinical characteristics and fetal outcomes were assessed. Results: Among the 227 eligible women, 177 (78.0%) were allocated to the mild group and 50 (22.0%) were in the severe group. Women with severe ICP also had a significantly higher incidence of planned and unplanned CS compared with mild ICP subjects (52.0% vs 23.7% and 22.0% vs 6.8%, respectively; p < 0.001). The indications for CS showed that fetal intolerance (65.4% vs 14.3%) was higher in severe ICP compared with mild ICP (p < 0.001). Severe ICP was associated with an increased risk of preterm delivery (p < 0.001), low birthweight (p＝0.001), and neonatal intensive care unit (NICU) admission (p < 0.001). Women with severe ICP (OR 6.397, 95%CI 3.041-13.455, p < 0.001) or preeclampsia (OR 12.434, 95%CI 5.166-29.928, p < 0.001) had increased risks of AFOs compared to controls. Conclusions: Severe ICP and preeclampsia are associated with a higher incidence of AFOs.